Mindfulness Sebagai Metode untuk Mengurangi Stres Akademik pada Mahasiswa - Alifah Izzah Al Islamiyah; Della Fitriyah; Malika Ummi Rahmania; Nazhifa Resti Agmalia; Rika Nofianti (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Academic stress is one of the most common psychological problems experienced by university students due to various academic demands during higher education. Assignments, examinations, academic achievement expectations, limited time management, and social pressures often contribute to physical and psychological exhaustion among students. If not properly managed, academic stress may negatively affect concentration, motivation, mental health, and academic performance. One approach widely applied in positive psychology to manage stress is mindfulness. Mindfulness refers to an individual's ability to pay attention intentionally to present-moment experiences with openness, acceptance, and non-judgment. This community service program aimed to improve students' ability to apply mindfulness as a strategy for managing academic stress. The program was conducted over two weeks through four sessions consisting of self-awareness activities, mindfulness psychoeducation, meditation practice, thought-card games, reflection sessions, and evaluation through pre-test and post-test assessments. The participants consisted of 5–6 university students experiencing academic stress. The instruments used were the Mindfulness Attention Awareness Scale (MAAS) and the Perceived Stress Scale (PSS). The results indicated increased understanding of mindfulness, improved emotional regulation skills, and reduced academic stress levels among participants. These findings suggest that mindfulness can be an effective method to help students cope with academic pressure adaptively and enhance their psychological well-being.